Modelling artificial intelligence in economics - Gries, Thomas; Naudé, Wim (Journal for Labour Market Research)
Abstract We provide a partial equilibrium model wherein AI provides abilities combined with human skills to provide an aggregate intermediate service good. We use the model to find that the extent of automation through AI will be greater if (a) the economy is relatively abundant in sophisticated programs and machine abilities compared to human skills; (b) the economy hosts a relatively large number of AI-providing firms and experts; and (c) the task-specific productivity of AI services is relatively high compared to the task-specific productivity of general labor and labor skills. We also illustrate that the contribution of AI to aggregate productive labor service depends not only on the amount of AI services available but on the endogenous number of automated tasks, the relative productivity of standard and IT-related labor, and the substitutability of tasks. These determinants also affect the income distribution between the two kinds of labor. We derive several empirical implications and identify possible future extensions.
Keywords: General Medicine

17 Use Cases for Analyzing Use Phase Data in Product Planning of Manufacturing Companies - Meyer, Maurice; Panzner, Melina; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Why make it hard? - Usage of aggregated statistical data for risk assessment of damage scenarios in the context of ISO/SAE 21434 - Japs, Sergej; Kargl, Frank; Anacker, Harald; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Requirements analysis for an intelligent workforce planning system: a socio-technical approach to design AI-based systems - Gabriel, Stefan; Bentler, Dominik; Grote, Eva-Maria; Junker, Caroline; Wendischhoff, David Meyer zu; Bansmann, Michael; Latos, Benedikt; Hobscheidt, Daniela; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Cross-industry methods for strategic planning of the digital transformation of small and medium sized enterprises - Förster, Magdalena; Kürpick, Christian; Hobscheidt, Daniela; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Security- and Safety-Driven Functional Architecture Development Exemplified by Automotive Systems Engineering - Kharatyan, Aschot; Günther, Matthias; Anacker, Harald; Japs, Sergej; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Method for direct end customer integration into the agile product development - Humpert, Lynn; Röhm, Benjamin; Anacker, Harald; Dumitrescu, Roman; Anderl, Reiner (Procedia CIRP)
Keywords: General Medicine

Collaborative Modeling of Interoperable Digital Twins in a SoS Context - Göllner, Denis; Rasor, Rik; Anacker, Harald; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Business-to-Analytics Canvas - Translation of Product Planning-Related Business Use Cases into Concrete Data Analytics Tasks - Panzner, Melina; Meyer, Maurice; Enzberg, Sebastian von; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Value Creation Framework and Roles for Smart Services - Reinhold, Jannik; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Sixteen-week multicentre randomised controlled trial to study the effect of the consumption of an oat beta-glucan-enriched bread versus a whole-grain wheat bread on glycaemic control among persons with pre-diabetes: a study protocol of the CarbHealth study - Hjorth, Therese; Schadow, Alena; Revheim, Ingrid; Spielau, Ulrike; Thomassen, Lise M; Meyer, Klara; Piotrowski, Katja; Rosendahl-Riise, Hanne; Rieder, Anne; Varela, Paula; Lysne, Vegard; Ballance, Simon; et al. (BMJ Open)
Introduction In 2012, the estimated global prevalence of pre-diabetes was 280 million, and the prevalence is expected to rise to 400 million by 2030. Oat-based foods are a good source of beta-glucans, which have been shown to lower postprandial blood glucose. Studies to evaluate the effectiveness of the long-term intake of beta-glucan-enriched bread as part of a habitual diet among individuals with pre-diabetes are needed. Therefore, we designed a multicentre intervention study in adults with pre-diabetes to investigate the effects of consumption of an oat-derived beta-glucan-enriched bread as part of a normal diet on glycated haemoglobin (HbA1c) in comparison to consumption of whole-grain wheat bread. Methods and analysis The CarbHealth trial is a multicentre double-blind randomised controlled 16-week dietary intervention trial in participants 40–70 years of age with a body mass index of ≥27 kg/m 2 and HbA1c of 35–50 mmol/mol. The study is conducted at four universities located in Norway, Sweden and Germany and uses intervention breads specifically designed for the trial by Nofima AS. The aim is to recruit 250 participants. The primary outcome is the difference in HbA1c between the intervention and the control groups. The main analysis will include intervention group, study centre and baseline HbA1c as independent variables in an analysis of covariance model. Ethics and dissemination The study protocol was approved by respective ethical authorities in participating countries. The results of the study will be communicated through publication in international scientific journals and presentations at (inter)national conferences. Trial registration number NCT04994327 .
Keywords: General Medicine

Nutzungsverhalten von Lehrkräften bei der Implementierung einer physikdidaktisch innovativen Unterrichtskonzeption - Breuer, Judith; Vogelsang, Christoph; Reinhold, Peter (Zeitschrift für Didaktik der Naturwissenschaften)
Zusammenfassung Eine zentrale Aufgabe fachdidaktischer Forschung stellt die Verbesserung schulischen Unterrichts dar. Die freie Bereitstellung wirksamer Unterrichtskonzeptionen zur Unterstützung des Selbststudiums von Lehrkräften bildet eine Strategie für eine flächendeckende Implementierung fachdidaktischer Innovationen. Allerdings etablieren sich zahlreiche, empirisch erfolgreich evaluierte Unterrichtskonzeptionen nicht nachhaltig an Schulen. Daher untersucht das vorliegende Forschungsvorhaben den Implementationsprozess solcher Materialien unter authentischen Bedingungen. Dazu wurde kriteriengeleitet eine evidenzbasierte, fachdidaktisch innovative Unterrichtskonzeption ausgewählt: das Münchener Unterrichtskonzept zur Quantenmechanik (MILQ). Diese wurde den teilnehmenden Lehrkräften fakultativ zur Verfügung gestellt. Mittels Fallstudien wurde die Implementierung von MILQ von elf Lehrkräften durch halbstandardisierte Interviews zu Beginn und am Ende einer Unterrichtsreihe zur Quantenmechanik sowie zwei Unterrichtsbeobachtungen mit je einem anschließenden stimulated recall explorativ erfasst. Die Probanden setzten sich überwiegend heuristisch mit MILQ auseinander und implementierten vor allem Elemente auf Sichtstrukturebene im Unterricht, die konform zu ihren bisherigen Vorstellungen waren. Dadurch wurde das fachdidaktische Innovationspotential nicht ausgeschöpft. Bezeichnend ist, dass der empirische Wirksamkeitsnachweis von MILQ für die Beurteilung der Lehrkräfte nicht relevant war, was aus theoretischer Sicht bislang als ein zentrales Argument der Bereitstellungsstrategie zur Implementierung fachdidaktischer Innovation angenommen wurde.
Keywords: General Medicine

High‐Resolution Study of Changes in Morphology and Chemistry of Cylindrical PS‐ b ‐PMMA Block Copolymer Nanomasks during Mask Development - Bürger, Julius; Venugopal, Harikrishnan; Kool, Daniel; de los Arcos de Pedro, Maria Teresa; Gonzalez Orive, Alejandro; Grundmeier, Guido; Brassat, Katharina; Lindner, Jörg (Advanced Materials Interfaces)
Keywords: General Medicine

Accessibility properties of abnormal geodesics in optimal control illustrated by two case studies - Bonnard, Bernard; Rouot, Jérémy; Wembe Moafo, Boris Edgar (Mathematical Control and Related Fields)
Keywords: Applied Mathematics; Control and Optimization; General Medicine

Development of operational and demand-oriented firefighting equipment - Hanses, Hendrik; Horwath, Ilona (Materials Today: Proceedings)
Keywords: General Medicine

Rumor Correction in Social Media Crisis Communication: A Case of Connective Sense-Breaking - Mirbabaie, Milad; Marx, Julian; Reimann, Annette (AIS Transactions on Human-Computer Interaction)
Keywords: General Medicine

Stiffness optimization and reliable design of a hip implant by using the potential of additive manufacturing processes - Risse, Lena; Woodcock, Steven Clifford; Brüggemann, Jan-Peter; Kullmer, Gunter; Richard, Hans Albert (BioMedical Engineering OnLine)
Abstract Background Due to the steadily increasing life expectancy of the population, the need for medical aids to maintain the previous quality of life is growing. The basis for independent mobility is a functional locomotor system. The hip joint can be so badly damaged by everyday wear or accelerated by illness that reconstruction by means of endoprostheses is necessary. Results In order to ensure a high quality of life for the patient after this procedure as well as a long service life of the prosthesis, a high-quality design is required, so that many different aspects have to be taken into account when developing prostheses. Long-term medical studies show that the service life and operational safety of a hip prosthesis by best possible adaptation of the stiffness to that of the bone can be increased. The use of additive manufacturing processes enables to specifically change the stiffness of implant structures. Conclusions Reduced implant stiffness leads to an increase in stress in the surrounding bone and thus to a reduction in bone resorption. Numerical methods are used to demonstrate this fact in the hip implant developed. The safety of use is nevertheless ensured by evaluating and taking into account the stresses that occur for critical load cases. These results are a promising basis to enable longer service life of prostheses in the future.
Keywords: Radiology; Nuclear Medicine and imaging; Biomedical Engineering; General Medicine; Biomaterials; Radiological and Ultrasound Technology

Information Model for Hybrid Prototyping in Design Reviews of Assembly Stations - Gräßler, Iris; Roesmann, Daniel; Hillebrand, Stefan; Pottebaum, Jens (Procedia CIRP ICME)
Keywords: General Medicine

Influence of the incident angle on the OCT measurement during remote laser beam welding - Werner, Matthias; Wagner, Jonas; Ribbeck, Florian; Hensel, Simon; Goth, Klaus; Graf, Thomas; Meschut, Gerson (Procedia CIRP)
Keywords: General Medicine

Microstructure and corrosion properties of PBF-LB produced carbide nanoparticles additivated AlSi10Mg parts - Kusoglu, Ihsan Murat; Vieth, Pascal; Heiland, Steffen; Huber, Florian; Lüddecke, Arne; Ziefuss, Anna Rosa; Kwade, Arno; Schmidt, Michael; Schaper, Mirko; Barcikowski, Stephan; Grundmeier, Guido (Procedia CIRP)
Keywords: General Medicine

Comparing lab and field agility kinematics in young talented female football players: Implications for ACL injury prevention - Di Paolo, Stefano; Nijmeijer, Eline; Bragonzoni, Laura; Dingshoff, Evelien; Gokeler, Alli; Benjaminse, Anne (European Journal of Sport Science)
Keywords: Orthopedics and Sports Medicine; Physical Therapy; Sports Therapy and Rehabilitation; General Medicine

Parameterized Complexity of Logic-Based Argumentation in Schaefer's Framework - Mahmood, Yasir; Meier, Arne; Schmidt, Johannes (Proceedings of the AAAI Conference on Artificial Intelligence)
Logic-based argumentation is a well-established formalism modeling nonmonotonic reasoning. It has been playing a major role in AI for decades, now. Informally, a set of formulas is the support for a given claim if it is consistent, subset-minimal, and implies the claim. In such a case, the pair of the support and the claim together is called an argument. In this paper, we study the propositional variants of the following three computational tasks studied in argumentation: ARG (exists a support for a given claim with respect to a given set of formulas), ARG-Check (is a given set a support for a given claim), and ARG-Rel (similarly as ARG plus requiring an additionally given formula to be contained in the support). ARG-Check is complete for the complexity class DP, and the other two problems are known to be complete for the second level of the polynomial hierarchy and, accordingly, are highly intractable. Analyzing the reason for this intractability, we perform a two-dimensional classification: first, we consider all possible propositional fragments of the problem within Schaefer's framework, and then study different parameterizations for each of the fragment. We identify a list of reasonable structural parameters (size of the claim, support, knowledge-base) that are connected to the aforementioned decision problems. Eventually, we thoroughly draw a fine border of parameterized intractability for each of the problems showing where the problems are fixed-parameter tractable and when this exactly stops. Surprisingly, several cases are of very high intractability (paraNP and beyond).
Keywords: General Medicine

Talking without a Voice: Virtual Co-Speakership in an Educational Webinar - A. Erofeeva, Maria; Klowait, Nils; Kimstach, Uliana (Sociology of Power)
Keywords: General Medicine

From Pure Art to Sheer Luxury: Magazines as Ornamental Constellations and the Emergence of Aesthetic Capitalism in the Early Twentieth Century - Gretz, Daniela; Krause, Marcus (Periodical Formats in the Market)
The concept of ‘ornamental constellations’ introduced in the following article highlights the structural relationships of decorative elements and miscellaneous content in magazines and the importance of the reader’s perspective for their interpretation. ‘Ornamental constellations’ are considered one of the most important media devices of emerging aesthetic capitalism, as they produce economies of attention and affect and establish a visual connection between the basic concept of a magazine, its individual contributions, and the readership addressed, thus promoting a specific aesthetic lifestyle. Their respective staging value is illustrated by analysing two complementary magazines and their constellation techniques: the elitist art magazine Blätter für die Kunst with its ‘strategic arrangement’ of literary and programmatic contributions and the creation of ‘resonances’ between them and the popular sports and society magazine Sport im Bild with its hybridizing flow of texts, images, and advertisements. Despite all the differences, it becomes clear that these are two quite compatible projects within the framework of an emerging aesthetic capitalism: whereas the Blätter für die Kunst staged and materialized the idea of pure art as an exclusive aesthetic lifestyle, the Sport im Bild made the desired aesthetic way of life also attainable by non-artists (with enough money) by associating it with the idea of an aesthetic capitalism.
Keywords: General Medicine

Introduction: English Linguistics, Learners and the Classroom - Hahn, Charlotte Anna; Mindt, Ilka (Anglistik)
Keywords: General Medicine

Mental Rotation of Tactic Board Instructions in Basketball: Domain-Specific Expertise Improves On-Court Performance - Krause, Daniel; Weigelt, Matthias (Research Quarterly for Exercise and Sport)
Keywords: Nephrology; Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine; General Medicine

Themes from the Philosophy of Robert Brandom - Bloch-Mullins, Corinne; Choi, Yoon H.; Luft, Sebastian (Journal of Transcendental Philosophy)
Keywords: General Medicine

‘Authentic Englishes.nrw’ – Developing and Using Interactive Teaching and Learning Materials on Varieties of English - Pape, S.; Fiege, Amanda Sophie; Mindt, Ilka (Anglistik)
Keywords: General Medicine

Modeling Feedback in Interaction With Conversational Agents—A Review - Axelsson, Agnes; Buschmeier, Hendrik; Skantze, Gabriel (Frontiers in Computer Science)
Intelligent agents interacting with humans through conversation (such as a robot, embodied conversational agent, or chatbot) need to receive feedback from the human to make sure that its communicative acts have the intended consequences. At the same time, the human interacting with the agent will also seek feedback, in order to ensure that her communicative acts have the intended consequences. In this review article, we give an overview of past and current research on how intelligent agents should be able to both give meaningful feedback toward humans, as well as understanding feedback given by the users. The review covers feedback across different modalities (e.g., speech, head gestures, gaze, and facial expression), different forms of feedback (e.g., backchannels, clarification requests), and models for allowing the agent to assess the user's level of understanding and adapt its behavior accordingly. Finally, we analyse some shortcomings of current approaches to modeling feedback, and identify important directions for future research.
Keywords: General Medicine

On the lower operation limit and the gain of flexibility of an innovative segmented tray column - Fasel, Henrik; Grünewald, Marcus; Riese, Julia (Journal of Advanced Manufacturing and Processing)
Abstract Operating windows of conventional tray columns may not be large enough to ensure a sufficient separation with the current or future challenges of a volatile energy and raw material supply. Therefore, an innovative, segmented separation tray has been developed, which enlarges the operation window and thus leads to a higher flexibility, managing the challenges of higher volatility in downstream processes. In this contribution, a hydrodynamic characterization and the resulting lower operation limits of this segmented tray are presented. Furthermore, an approach to obtain shorter start‐up times for the column and a resulting faster response time to changes in the process are presented. The feasibility of this type of operation is evaluated by the investigation of the stability of the tray under new operation conditions.
Keywords: General Medicine

Rezension zu: Marianne Bechhaus-Gerst, Stefanie Michels, Fabian Fechner (Hg.): Nordrhein-Westfalen und der Imperialismus, Berlin 2022 - Hansen, Christin (Zeitschrift für Weltgeschichte)
Keywords: General Medicine

Rehabilitation strategies of Flemish physical therapists before and after anterior cruciate ligament reconstruction: An online survey - Dingenen, Bart; Billiet, Bart; De Baets, Liesbet; Bellemans, Johan; Truijen, Jan; Gokeler, Alli (Physical Therapy in Sport)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine; General Medicine

Extreme Events, Entrepreneurial Start-Ups, and Innovation: Theoretical Conjectures - Gries, Thomas; Naudé, Wim (Economics of Disasters and Climate Change)
Abstract In light of the COVID-19 pandemic, we scrutinize what has been established in the literature on whether entrepreneurship can cause and resolve extreme events, the immediate and long-run impacts of extreme events on entrepreneurship, and whether extreme events can positively impact (some) entrepreneurship and innovation. Based on this, we utilize a partial equilibrium model to provide several conjectures on the impact of COVID-19 on entrepreneurship, and to derive policy recommendations for recovery. We illustrate that while entrepreneurship recovery will benefit from measures such as direct subsidies for start-ups, firms’ revenue losses, and loan liabilities, it will also benefit from aggregate demand-side support and income redistribution measures, as well as from measures that facilitate the innovation-response to the Keynesian supply-shock caused by the pandemic, such as access to online retail and well-functioning global transportation and logistics.
Keywords: General Medicine

Maturity-based Development of Strategic Thrusts for Socio-technical Risks - Menzefricke, Joern Steffen; Wiederkehr, Ingrid; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Ebenen der genetischen Analyse komplexer Phänotypen am Beispiel der Anorexia nervosa und der Varianz des Körpergewichts - Hirtz, Raphael; Zheng, Yiran; Rajcsanyi, Luisa S.; Libuda, Lars; Antel, Jochen; Peters, Triinu; Hebebrand, Johannes; Hinney, Anke (Zeitschrift für Kinder- und Jugendpsychiatrie und Psychotherapie)
Zusammenfassung. Genetische Varianten beeinflussen die Gewichtsregulation und die Entwicklung von Essstörungen. Zunächst haben familienbasierte, sogenannte formalgenetische Studien den erblichen Anteil an der Gewichtsregulation und an der Ätiologie von Essstörungen beleuchtet. In einer Vielzahl von Studien zeigten sich sowohl für die Varianz des Körpergewichts als auch für die Entstehung von Essstörungen Erblichkeitsschätzer (Heritabilitätsraten) von über 50 %. Mit diesem Wissen begab man sich in den 90er-Jahren des letzten Jahrhunderts auf die Suche nach den zugrundeliegenden Genen (genauer: genetischen Varianten), die das Körpergewicht, das Essverhalten oder beide Phänotypen auf Grundlage geteilter Mechanismen beeinflussen. Zunächst wurden Kandidatengenstudien durchgeführt. Dabei untersuchte man auf Grundlage unterschiedlicher, v. a. aber pathophysiologisch plausibler Überlegungen Gene mit hoher Relevanz für die untersuchten Phänotypen. Dieser Ansatz war für Essstörungen nicht sehr erfolgreich, für die Gewichtsregulation konnte eine Handvoll Gene identifiziert werden. Verbunden mit großen methodischen Fortschritten in der genetischen Forschung und v. a. der Etablierung sogenannter genomweiter Assoziationsstudien (GWAS) Anfang der 2000er-Jahre konnten bislang über 1000 Varianten/Genorte detektiert werden, die das Körpergewicht beeinflussen. Für die Essstörung Anorexia nervosa (AN) sind aktuell acht solcher Genorte beschrieben. Diese Ergebnisse, aber auch aktuelle Ansätze zu phänotypübergreifenden Analysen lassen Einblicke in die komplexe Regulation des Körpergewichtes zu und haben zudem unerwartete Pathomechanismen für AN aufgezeigt.
Keywords: Psychiatry and Mental health; Clinical Psychology; General Medicine; Pediatrics; Perinatology and Child Health

Maturity-based Development of Strategic Thrusts for Socio-technical Risks - Menzefricke, Jörn Steffen; Wiederkehr, Ingrid; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

AMPA-15N – Synthesis and application as standard compound in traceable degradation studies of glyphosate - Wirth, Marisa A.; Longwitz, Lars; Kanwischer, Marion; Gros, Peter; Leinweber, Peter; Werner, Thomas (Ecotoxicology and Environmental Safety)
Keywords: Health; Toxicology and Mutagenesis; Public Health; Environmental and Occupational Health; Pollution; General Medicine

Chancen des inklusionsorientierten Sachunterrichts für didaktisch-diagnostisches Handeln. Konzeptionelle und methodologisch-methodische Grundlagen eines forschungsbasierten Entwicklungsansatzes für die Lehrer*innenbildung - Schroeder, René; Blumberg, Eva; Kottmann, Brigitte; Miller, Susanne; Reh, Anne (QfI - Qualifizierung für Inklusion. Online-Zeitschrift zur Forschung über Aus-, Fort- und Weiterbildung pädagogischer Fachkräfte)
In der Herausforderung Unterricht inklusionsbezogen weiterzuentwickeln, manifestiert sich unter anderem die Forderung nach der Qualifizierung von (angehenden) Lehrkräften bzgl. der Anwendung und Umsetzung einer alltagsintegrierten Diagnostik mit dem Ziel, Kinder individualisiert und gleichzeitig mit Bezug auf einen gemeinsamen Lerngegenstand zu unterrichten. Dabei ist ein didaktisch-diagnostisches Handeln aller Lehrkräfte gefordert, welches im Kontext einer professionellen und inklusionsorientierten Gestaltung sowie einer angemessenen Begleitung und Förderung von Lern- und Entwicklungsprozessen steht. In der Konzeption entsprechender Aus- und Weiterbildungsformate setzt das geplante Projekt DiPoSa (Didaktisch-diagnostische Potentiale des inklusionsorientierten Sachunterrichts) an. Ziel ist es durch einen Design-Based-Research-Ansatz (DBR) Videovignetten zu erstellen und zu evaluieren, mittels derer entsprechende Kompetenzen von (angehenden) Lehrkräften im Sachunterricht weiterentwickelt werden können. Dabei bietet insbesondere der Sachunterricht als vielperspektivisches Integrationsfach der Grundschule einen passenden Rahmen, kindliche Lernpotentiale als Ausgangspunkt für didaktisch-diagnostisches Handeln nutzbar zu machen. Denn in aktuellen inklusionsorientierten Ansätzen des Sachunterrichts sind sowohl reformpädagogisch orientierte als auch offene Konzepte und Modelle des adaptiven Unterrichts zu finden, die sich an den unterschiedlichen Programmatiken der Umsetzung von individueller Förderung orientieren. Im folgenden Beitrag werden die dem geplanten Projekt zugrundeliegenden theoretischen und empirischen Zugänge erläutert und die forschungsmethodische Umsetzung durch einen DBR-Ansatz als methodologische Basis für eine Theorie-Praxis-verzahnende Forschungsperspektive auf diagnostisches Handeln sowie die Förderung diagnostischer Handlungskompetenzen durch Videovignetten im Kontext der Aus- und Weiterbildung von (Sachunterrichts-)Lehrkräften diskutiert. Abstract The challenge to further promote practices of inclusive teaching, requires the development of assessment literacy. Combined with the aim to teach all children in a collaborative learning environment, qualification of teachers (in training) in the application and implementation of formative assessment as an integrated daily routine is needed. Therefore, the project DiPoSa focuses on the development of appropriate training and qualification formats. The project heads to create and evaluate video vignettes using a design-based-research approach (DBR), which can then be used to further develop assessment literacy of teachers in social studies and science in primary education. As a multi-perspective integrative subject in elementary school social studies and science in primary education offers a suitable framework for practices of formative assessment taking children's learning potentials as a serious concern. Foundations can be seen in current inclusive approaches to social studies and science in primary education, where reform pedagogically orientation and open concepts can as well be found as models of adaptive teaching. Although there are different theoretical and programmatic implementations, both perspectives share an orientation towards individual support of children. With this in mind the following article tries to lay down the theoretical and empirical approaches of the planed project DiPoSa and discusses methodological foundations of the project. The discussion focuses on how assessment practices as well as assessment literacy can be promoted through a DBR research-design using video vignettes in the context of teacher education and qualification and rooting in a deepened science-practice partnership.Zusammenfassung englisch
Keywords: General Medicine

Learning to play golf for elderly people with subjective memory complaints: feasibility of a single‐blinded randomized pilot trial - Stroehlein, Julia K.; Vieluf, Solveig; Zimmer, Philipp; Schenk, Alexander; Oberste, Max; Gölz, Christian Johannes; van den Bongard, Franziska; Reinsberger, Claus (BMC Neurology)
Abstract Background Subjective Memory Complaints (SMC) in elderly people due to preclinical Alzheimer’s Disease may be associated with dysregulation of the Kynurenine Pathway (KP), with an increase in neurotoxic metabolites that affect cognition. Golf is a challenging sport with high demands on motor, sensory, and cognitive abilities, which might bear the potential to attenuate the pathological changes of preclinical AD. This trial investigated the feasibility of learning to play golf for elderly with cognitive problems and its effects on cognitive functions and the KP. Methods In a 22-week single-blinded randomized controlled trial, elderly people with SMC were allocated to the golf ( n = 25, 180 min training/week) or control group ( n = 21). Primary outcomes were feasibility (golf exam, adherence, adverse events) and general cognitive function (Alzheimer’s Disease Assessment Scale). Secondary outcomes include specific cognitive functions (Response Inhibition, Corsi Block Tapping Test, Trail Making Test), KP metabolites and physical performance (6-Minute-Walk-Test). Baseline-adjusted Analysis-of-Covariance was conducted for each outcome. Results 42 participants were analyzed. All participants that underwent the golf exam after the intervention passed it (20/23). Attendance rate of the golf intervention was 75 %. No adverse events or drop-outs related to the intervention occurred. A significant time*group interaction ( p = 0.012, F = 7.050, Cohen’s d = 0.89) was found for correct responses on the Response Inhibition task, but not for ADAS-Cog. Moreover, a significant time*group interaction for Quinolinic acid to Tryptophan ratios ( p = 0.022, F = 5.769, Cohen’s d = 0.84) in favor of the golf group was observed. An uncorrected negative correlation between attendance rate and delta Quinolinic acid to Kynurenic acid ratios in the golf group ( p = 0.039, r =-0.443) was found as well. Conclusions The findings indicate that learning golf is feasible and safe for elderly people with cognitive problems. Preliminary results suggest positive effects on attention and the KP. To explore the whole potential of golfing and its effect on cognitive decline, a larger cohort should be studied over a longer period with higher cardiovascular demands. Trial registration The trial was retrospectively registered (2nd July 2018) at the German Clinical Trials Register ( DRKS00014921 ).
Keywords: Clinical Neurology; General Medicine

Application of engineering methods in the planning process of surgical treatments - Risse, Lena; Kullmer, Gunter (Journal of 3D Printing in Medicine)
The continuous development of medical methods in recent decades has achieved measurable improvement. The interdisciplinary cooperation of engineers and physicians is a forward-looking component of this development. However, this cooperation also results in new interfaces on the communication and software level, which must be defined by implementing a systematic workflow. In this paper, the step-by-step implementation of engineering methods into the surgical workflow is shown. The focus is on the basic requirements and the necessary exchange of information. Additively manufactured models for preoperative elucidation of the patient are used as a psychological added value to increase the transparency of the surgical procedure. In addition, the models serve to train young surgeons and provide the opportunity to plan advanced surgical techniques.
Keywords: General Medicine

Reintroduction of Running After Anterior Cruciate Ligament Reconstruction With a Hamstrings Graft: Can We Predict Short-Term Success? - Pairot de Fontenay, Benoit; Van Cant, Joachim; Gokeler, Alli; Roy, Jean-Sébastien (Journal of Athletic Training)
Context Return to running (RTR) after anterior cruciate ligament reconstruction (ACLR) is a crucial milestone. However, how and when to start a running program are uncertain. Objective To explore the feasibility of a structured program to reintroduce running after ACLR and evaluate the predictive value of potential predictors of short-term success. Design Longitudinal cohort study. Setting Local research center and participants' homes. Patients or Other Participants Thirty-five participants were recruited after ACLR. Intervention(s) Program with a progression algorithm to reintroduce running (10 running sessions in 14 days). Main Outcome Measure(s) The criterion for short-term success was no exacerbation of symptoms. Potential predictors were (1) the International Knee Documentation Committee (IKDC) subjective knee form score, (2) ACL Return to Sport after Injury questionnaire score, (3) quadriceps and hamstrings strength, (4) step-down endurance test, and (5) modified Star Excursion Balance test. Descriptive statistics were performed to study the feasibility of the RTR program, and Poisson regression analysis was used to evaluate predictors of success. Results Of the 34 participants, 33 completed the RTR program. Sixteen participants experienced some temporary exacerbation of symptoms, but only 1 had to stop the program. The initial IKDC score was the only significant predictor of a successful RTR, with an area under the receiver operating characteristic curve of 80.4%. An IKDC cut-off of 63.7/100 differentiated responders and nonresponders with the highest sensitivity and specificity (77.8% and 75.0%, respectively). A participant with an IKDC score above this threshold had a 3-fold greater chance of success. Conclusions Our results confirm the feasibility of our RTR program and progression algorithm after ACLR. Clinicians should use an IKDC score of >64 as a criterion to reintroduce running after ACLR to increase the likelihood of short-term success.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine; General Medicine

Rehabilitation strategies of Flemish physical therapists before and after anterior cruciate ligament reconstruction: An online survey - Dingenen, Bart; Billiet, Bart; De Baets, Liesbet; Bellemans, Johan; Truijen, Jan; Gokeler, Alli (Physical Therapy in Sport)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine; General Medicine

Examining the Perceptual-Cognitive Mechanism of Deceptive Actions in Sports - Polzien, Andrea; Güldenpenning, Iris; Weigelt, Matthias (Experimental Psychology)
Abstract. In several kinds of sports, deceptive actions are used to hinder the anticipation performance of an opponent. During a head fake in basketball, a player turns the head to one side but passes the ball to the other side. A pass with a head fake generates a head-fake effect in the observer, which is characterized by slower and more error-prone responses to the pass direction as compared to passes without a head fake. Whereas the head-fake effect has been replicated several times, the question of its origin with dynamic stimuli has not been answered yet. The present study includes four experiments, which are conducted to examine the perceptual-cognitive mechanism underlying the effect by using the model of dimensional overlap ( Kornblum et al., 1990 ) and the additive factors logic ( Sternberg, 1969 ). Results point to multiple processes contributing to the head-fake effect for dynamic stimuli, which operate not only at a perceptual level but also at a level of response selection.
Keywords: General Psychology; Arts and Humanities (miscellaneous); Experimental and Cognitive Psychology; General Medicine

Cassirer’s Children, Special Topics Issue
Keywords: General Medicine

Nickl, Benjamin; Popenici, Stefan; Blackler, Deane (Hrsg.): Transnational German Education and Comparative Education Systems. Research and Practice. Cham: Springer, 2020 (Global Germany in transnational dialogues). -- ISBN 978-3-030-36254-6. 178 Seiten, € 72,79. - Schmidt, Eva (Informationen Deutsch als Fremdsprache)
Keywords: General Medicine

Vom Binge-Eating zu Yogakursen - Prikoszovits, Matthias (Sprache im Beruf)
Keywords: General Medicine

Restricting ankle dorsiflexion does not mitigate the benefits of external focus of attention on landing biomechanics in healthy females - Haines, Mackenzie; Murray, Amanda M.; Glaviano, Neal R.; Gokeler, Alli; Norte, Grant E. (Human Movement Science)
Keywords: Experimental and Cognitive Psychology; Orthopedics and Sports Medicine; General Medicine; Biophysics

Effects of 21 days of bed rest and whey protein supplementation on plantar flexor muscle fatigue resistance during repeated shortening contractions - Bosutti, Alessandra; Mulder, Edwin; Zange, Jochen; Bühlmeier, Judith; Ganse, Bergita; Degens, Hans (European Journal of Applied Physiology)
Abstract Purpose Space flight and bed rest (BR) lead to a rapid decline in exercise capacity. Whey protein plus potassium bicarbonate diet-supplementation (NUTR) could attenuate this effect by improving oxidative metabolism. We evaluated the impact of 21-day BR and NUTR on fatigue resistance of plantar flexor muscles (PF) during repeated shortening contractions, and whether any change was related to altered energy metabolism and muscle oxygenation. Methods Ten healthy men received a standardized isocaloric diet with ( n = 5) or without ( n = 5) NUTR. Eight bouts of 24 concentric plantar flexions (30 s each bout) with 20 s rest between bouts were employed. PF muscle size was assessed by means of peripheral quantitative computed tomography. PF muscle volume was assessed with magnetic resonance imaging. PF muscle force, contraction velocity, power and surface electromyogram signals were recorded during each contraction, as well as energy metabolism ( 31 P nuclear magnetic resonance spectroscopy) and oxygenation (near-infrared spectroscopy). Cardiopulmonary parameters were measured during an incremental cycle exercise test. Results BR caused 10–15% loss of PF volume that was partly recovered 3 days after re-ambulation, as a consequence of fluid redistribution. Unexpectedly, PF fatigue resistance was not affected by BR or NUTR. BR induced a shift in muscle metabolism toward glycolysis and some signs of impaired muscle oxygen extraction. NUTR did not attenuate the BR-induced-shift in energy metabolism. Conclusions Twenty-one days’ BR did not impair PF fatigue resistance, but the shift to glycolytic metabolism and indications of impaired oxygen extraction may be early signs of developing reduced muscle fatigue resistance.
Keywords: Physiology (medical); Public Health; Environmental and Occupational Health; Orthopedics and Sports Medicine; General Medicine; Public Health; Environmental and Occupational Health; Physiology

The impact of the 4th industrial revolution on the design fields of innovation management - Niewöhner, Nadine; Asmar, Laban; Röltgen, Daniel; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Physical activity and health promotion for nursing staff in elderly care: a study protocol for a randomised controlled trial - Otto, Ann-Kathrin; Pietschmann, Juliane; Appelles, Luisa-Marie; Bebenek, Michael; Bischoff, Laura L; Hildebrand, Claudia; Johnen, Bettina; Jöllenbeck, Thomas; Kemmler, Wolfgang; Klotzbier, Thomas; Korbus, Heide; Rudisch, Julian; et al. (BMJ Open)
Introduction Nursing staff is burdened by high workload and stress. Furthermore, heavy lifting, as well as transferring nursing home residents, cause lumbar tissue damage and back pain. Exercise intervention studies to reduce work-related problems are rare and the evidence for efficacy of studies among nurses is limited. Studies including targeted analysis of requirements are necessary to generate effective recommendations and tailored interventions for health promotion programmes. The purpose of this multicentred intervention study is to identify work-related problems, to implement health promotion programmes and to evaluate their effectiveness. Methods and analysis A randomised controlled trial will be conducted, including a total of 48 nursing home facilities in eight regions of Germany with an estimated sample size of 700 nurses. Standardised ergonomics and posture training (10 weeks, once a week for 20–30 min) and subsequently, back-fitness training (12 weeks, once a week for 45–60 min) will be administered. Following the implementation of standardised health promotion programmes, further demand-oriented interventions can be implemented. The perceived exposure to work-related demands, work-related pain in different parts of the body, health-related quality of life, perceived stress, work-related patterns of behaviour and experience, presentism behaviour, work environment as well as general needs and barriers to health promotion, will be assessed at baseline (pre-test), at 10 weeks (post-test, after ergonomics training), at 22 weeks (post-test, after back-fitness training) and at 34 weeks of the programme (follow-up). Ethics and dissemination The study was reviewed and approved by the local ethics committee of the University of Hamburg (AZ: 2018_168). The results of the study will be published in open-access and international journals. Furthermore, the results will be presented in the participating nursing homes and at national and international conferences. Trial registration number DRKS.de (DRKS00015241).
Keywords: General Medicine

The role of different directions of attention on the extent of implicit perception in soccer penalty kicking - Memmert, Daniel; Noël, Benjamin; Machlitt, Daniel; van der Kamp, John; Weigelt, Matthias (Human Movement Science)
Keywords: Experimental and Cognitive Psychology; Orthopedics and Sports Medicine; General Medicine; Biophysics

The Mental Rotation Ability of Expert Basketball Players: Identifying On-Court Plays - Weigelt, Matthias; Memmert, Daniel (Research Quarterly for Exercise and Sport)
Keywords: Nephrology; Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine; General Medicine

Restricting ankle dorsiflexion does not mitigate the benefits of external focus of attention on landing biomechanics in healthy females - Haines, Mackenzie; Murray, Amanda M.; Glaviano, Neal R.; Gokeler, Alli; Norte, Grant E. (Human Movement Science)
Keywords: Experimental and Cognitive Psychology; Orthopedics and Sports Medicine; General Medicine; Biophysics

Electrify your Game! Anodal tDCS Increases the Resistance to Head Fakes in Basketball - Friehs, Maximilian A.; Güldenpenning, Iris; Frings, Christian; Weigelt, Matthias (Journal of Cognitive Enhancement)
Keywords: General Medicine

Is the head-fake effect in basketball robust against practice? Analyses of trial-by-trial adaptations, frequency distributions, and mixture effects to evaluate effects of practice - Güldenpenning, Iris; Schütz, Christoph; Weigelt, Matthias; Kunde, Wilfried (Psychological Research)
Reactions to the pass of a basketball player performing a head fake are typically slower than reactions to a basketball player who passes without a head fake (i.e., head-fake effect). The present study shows that extensive practice reduces the head-fake effect in basketball. Additional analyses were conducted to explore the mechanism behind the reduced head-fake effect. First, we analyzed whether or not participants developed some control over the processing of irrelevant gaze direction, as indicated by specific trial-to-trial adaptations (i.e., congruency sequence effect). Second, we fitted the individual frequency distributions of RTs to ex-Gaussian distributions, to evaluate if practice specifically affects the Gaussian part of the distribution or the exponential part of the distribution. Third, we modeled individual RT distributions as the so-called mixture effects to examine whether the way irrelevant gaze direction impacts performance (either occasionally but massively or continuously but moderately) changes with practice. The analyses revealed that the effect of practice could not be explained with an increasing congruency-sequence effect. Also, it could not be found in the ex-Gaussian distributional analyses. The assumption that residual failure to inhibit the processing of the gaze direction in contrast to continuous failures to do so might favor mixed effects over uniform effects at later courses of practice could not be validated. The reduced head-fake effect thus is argued to source in participants’ general increasing ability to inhibit the processing of the task-irrelevant gaze direction information and/or in a priority shift of gaze processing to a processing of the pass direction.
Keywords: Arts and Humanities (miscellaneous); Developmental and Educational Psychology; Experimental and Cognitive Psychology; General Medicine

Cognitive load reduces interference by head fakes in basketball - Güldenpenning, Iris; Kunde, Wilfried; Weigelt, Matthias (Acta Psychologica)
Keywords: Arts and Humanities (miscellaneous); Developmental and Educational Psychology; Experimental and Cognitive Psychology; General Medicine

Zwischen romantischem Fragment und Skizze/n der Moderne. Zum medialen Realismus von Wilhelm Raabes "Wer kann es wenden?" - Gretz, Daniela (Jahrbuch der Raabe-Gesellschaft)
Keywords: General Medicine

Kant, Linnaeus, and the economy of nature - Wells, Aaron (Studies in History and Philosophy of Science Part C: Studies in History and Philosophy of Biological and Biomedical Sciences)
Keywords: History and Philosophy of Science; History; General Medicine

Zum praktischen Nutzen von Theorie. Ein Dialog über die Grenzen von Bildungspraxis, Erziehungswissenschaft und Soziologie - Haker, Christoph; Otterspeer, Lukas (Debatte. Beiträge zur Erwachsenenbildung)
Frank Beier, Franziska Wyßuwa und Elisa Wagner diskutieren in ihrem aktuellen Beitrag Fallinterpretationen zwischen Theorieund Anwendungsbezug den praktischen Nutzen wissenschaftlicher Erkenntnisse, insbesondere von Theorie, für die Schule und Erwachsenenbildung. Wir greifen ihre Position in einer dialogischen Replik kritisch auf. Die Form des Dialogs bietet uns die Möglichkeit, unsere Perspektiven als Erziehungswissenschaftler, Lehrer und Soziologe in die Debatte einzubringen. Wir möchten so die eingespielten Grenzziehungen in ‚Theorie- Praxis-Debatten‘ irritieren und Beiers, Wyßuwas und Wagners Plädoyer für die Stärke wissenschaftlicher Theorie ergänzen. Diese Stärke kommt weniger zur Geltung, wenn Theorie Kontingenz schließende und mehr, wenn sie Kontingenz öffnende Effekte hat. Zudem sollte Theorie nicht auf Modelle oder auf Theorien begrenzter Reichweite beschränkt und die konkrete Verwendung von Theorie zum Gegenstand der (Selbst)Reflexion und (Selbst)Kritik werden.
Keywords: Rehabilitation; Physical Therapy; Sports Therapy and Rehabilitation; General Medicine

A systematic approach to define flexibility in chemical engineering - Bruns, Bastian; Herrmann, Felix; Polyakova, Maria; Grünewald, Marcus; Riese, Julia (Journal of Advanced Manufacturing and Processing)
Abstract Increasing economic and environmental challenges leads to the need for changes in the chemical industry. In this context, a promising approach is utilizing flexible apparatuses and flexible plants to react to changing boundary conditions. However, the concept of flexibility in chemical engineering, which originated in manufacturing, still lacks a comprehensive organization and categorization of different types of flexibility. Thus, in this work, the origin of flexibility in manufacturing is traced, and a literature overview on flexibility in chemical engineering is provided. Based on a subsequent cluster analysis, four types of flexibility are identified and defined. Furthermore, this work enables research on flexibility to be integrated into a general and consistent definition of flexibility. The definitions are applied to examples from literature to achieve comparability. While enabling the qualitative assessment of flexibility, this work identifies open research gaps regarding the quantification of flexibility.
Keywords: General Medicine

Depth camera based statistical shape fitting approach for the creation of an individualized lower body biomechanical model: validity and reliability - Taetz, Bertram; Teufl, Wolfgang; Weidmann, Alexander; Pietschmann, Juliane; Jöllenbeck, Thomas; Bleser, Gabriele (Computer Methods in Biomechanics and Biomedical Engineering)
Keywords: Computer Science Applications; Human-Computer Interaction; Biomedical Engineering; General Medicine; Bioengineering

Dissociative effects of normative feedback on motor automaticity and motor accuracy in learning an arm movement sequence - Zobe, Christina; Krause, Daniel; Blischke, Klaus (Human Movement Science)
Keywords: Experimental and Cognitive Psychology; Orthopedics and Sports Medicine; General Medicine; Biophysics

Erziehungswissenschaft als Verunsicherungswissenschaft. Nicht nur eine Kritik des Mobilitätsimperativs - Haker, Christoph; Otterspeer, Lukas (Debatte. Beiträge zur Erwachsenenbildung)
Sebastian Zicks erziehungswissenschaftliche Kritik des Mobilitätsimperativs ist Ausgangspunkt unseres Beitrags. Wir greifen diese Kritik auf, indem wir sie in zweifacher Hinsicht ergänzen: Erstens um einen Fokus auf soziale Mobilität, welche sich in Mobilitätsnarrativen mit räumlicher Mobilität als verwoben zeigt. Zweitens um die Perspektive auf Mobilität als Rückkehr, die wir von einer Perspektive auf Mobilität als Fortbewegung abgrenzen. Die Rückwärtsbewegung ist für uns eng an (Selbst-)Reflexionen und transformatorische Bildungsprozesse gebunden, wie sie in Didier Eribons autosozioanalytischem Vorhaben einer Rückkehr zu erkennen sind. Unsere Ausführungen münden erstens in einer Kritik am Imperativ des Bildungsaufstiegs, in dem mehr Bildung scheinbar immer mit individuellen und kollektiven Fortschritten einhergeht. Zweitens wenden wir die von uns herausgearbeitete Kritik reflexiv auf die Erziehungswissenschaft. Sie ist dann eine Verunsicherungswissenschaft, für die die Rückkehr, und damit das Hinterfragen eigener Selbstverständlichkeiten, konstitutiv ist.
Keywords: Rehabilitation; Physical Therapy; Sports Therapy and Rehabilitation; General Medicine

Zur Berufsorientierung südeuropäischer DaF-Hochschullehrpläne - Prikoszovits, Matthias (Sprache im Beruf)
Keywords: General Medicine

Technikfolgenabschätzung als Zeitdiagnose - Alpsancar, Suzana (TATuP - Zeitschrift für Technikfolgenabschätzung in Theorie und Praxis)
Ropohl plädiert in seiner Technikphilosophie für eine bewusste Gestaltung des technischen Wandels, in dem auch die Ingenieur*innen in die Pflicht genommen werden. In meiner Rekonstruktion zeige ich, dass Ropohls normative Grundorientierung in einer Zeitdiagnose fußt, die er allerdings nicht expliziert. Aus seinem Beispiel ziehe ich die These, dass jeder Theorie der Technikfolgenabschätzung (TA) notwendig eine historisch-normative Signatur eingeschrieben ist. Um eine kritische Auseinandersetzung über das Selbstverständnis und den Zweck von TA zu führen, gilt es, anders als Ropohl, auch die inhärenten Zeitdiagnosen sichtbar zu machen und zu diskutieren.
Keywords: General Medicine

Machine learning and natural language processing on the patent corpus: Data, tools, and new measures - Balsmeier, Benjamin; Assaf, Mohamad; Chesebro, Tyler; Fierro, Gabe; Johnson, Kevin; Johnson, Scott; Li, Guan‐Cheng; Lück, Sonja; O'Reagan, Doug; Yeh, Bill; Zang, Guangzheng; Fleming, Lee (Journal of Economics & Management Strategy)
Drawing upon recent advances in machine learning and natural language processing, we introduce new tools that automatically ingest, parse, disambiguate, and build an updated database using U.S. patent data. The tools identify unique inventor, assignee, and location entities mentioned on each granted U.S. patent from 1976 to 2016. We describe data flow, algorithms, user interfaces, descriptive statistics, and a novelty measure based on the first appearance of a word in the patent corpus. We illustrate an automated coinventor network mapping tool and visualize trends in patenting over the last 40 years.
Keywords: Management of Technology and Innovation; Strategy and Management; Economics and Econometrics; General Business; Management and Accounting; General Medicine

Special Issue: Predictive Security Technologies (Editorial) - Hälterlein, Jens; Ostermeier, Lars (European Journal for Security Research)
Keywords: General Medicine

Vom One-Stop-Shop zum Wühltisch? - Prikoszovits, Matthias; Springer, Bernd F.W. (Informationen Deutsch als Fremdsprache)
Zusammenfassung Der vorliegende Beitrag fokussiert den Wandel und die Neuerungen innerhalb der Germanistik der Universitat Autònoma de Barcelona (UAB) anhand eines Abrisses über die lokalspezifischen Entwicklungslinien des Studiengangs seit den 1980er Jahren. In den späten 2000er und den aktuellen 2010er Jahren waren und sind die lokalen Entwicklungen stark von den Auswirkungen der 2008 ausgebrochenen Wirtschaftskrise geprägt, die Spanien mit besonderer Härte getroffen und durch die damit verbundenen Stellenstreichungen auch das aktuelle Unterrichtskonzept der Germanistik und des DaF-Unterrichts der UAB beeinflusst hat. Nach Erläuterungen zu diesem Unterrichtskonzept werden abschließend die Herausforderungen und Perspektiven im Bereich der künftigen instituts- und lokalspezifischen Curriculumplanung erläutert.
Keywords: General Medicine

Ott, Friederike: Deutsch für den Berufseinstieg: Der Sprachkurs zur Erstorientierung am Arbeitsplatz. München: Langenscheidt, 2017. – ISBN 978-3-468-48972-3. 64 Seiten, € 9,99. - Prikoszovits, Matthias (Informationen Deutsch als Fremdsprache)
Keywords: General Medicine

Auf dem Weg zur Smart Factory: modulare, intelligente Konzepte für die Produktion von Spezialchemikalien der Zukunft - Reitze, Arnulf; Jürgensmeyer, Nikolas; Lier, Stefan; Kohnke, Marco; Riese, Julia; Grünewald, Marcus (Angewandte Chemie)
Abstract Die Digitalisierung und Flexibilisierung von Produktionsprozessen bieten in der Spezialchemie die Chance, auf marktseitige Herausforderungen adäquat zu reagieren. Kürzer werdende Produktlebenszyklen, zunehmende Produktindividualisierung und die daraus resultierende Volatilität der Märkte stellen neue Anforderungen an Anlagenbetreiber. Neuartige Konzepte wie modulare Produktionsanlagen sowie Technologieentwicklungen im Rahmen der Industrie 4.0 können dabei helfen, die Smart Factory in der Spezialchemie umzusetzen. Im Folgenden werden die für diesen Wandel notwendigen Konzepte vorgestellt.
Keywords: General Medicine

Low-voltage C 8 -BTBT thin-film transistors for flexible electronics - Meyers, Thorsten; Vidor, Fabio F.; Puls, Charlotte; Hilleringmann, Ulrich (Materials Today: Proceedings)
Keywords: General Medicine

Ein universitäres DaF-Unterrichtsprojekt im Spiegel von Curriculumdiskussion und berufsbezogenem Fremdsprachenunterricht - Prikoszovits, Matthias (Informationen Deutsch als Fremdsprache)
Zusammenfassung Im Beitrag wird zunächst erläutert, wie sich Curriculumforschung und berufsbezogenes Lernen und Lehren im Bereich Deutsch als Fremdsprache seit den 1990er Jahren entwickelt haben, um in einem weiteren Schritt zu beschreiben, wie sich ein konkretes Unterrichtsprojekt in die DaF-Curriculumdiskussion eingliedert. Dabei wird vor allem auf die Frage eingegangen, ob die Forderung nach einer Berufsorientierung im universitären Fremdsprachenunterricht mit dem Unterrichtsprojekt umgesetzt wurde. Untersuchungsgegenstand ist eine im Jahr 2014 an der Germanistik der University of St Andrews (Schottland, GB) durchgeführte, benotete Projektarbeit, bei der Studierende des vierten und letzten Studienjahres Werbeclips drehen mussten.
Keywords: General Medicine

Mental Rotation of Tactical Instruction Displays Affects Information Processing Demand and Execution Accuracy in Basketball - Koopmann, Till; Steggemann-Weinrich, Yvonne; Baumeister, Jochen; Krause, Daniel (Research Quarterly for Exercise and Sport)
Keywords: Nephrology; Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine; General Medicine

Mental Rotation of Tactical Instruction Displays Affects Information Processing Demand and Execution Accuracy in Basketball - Koopmann, Till; Steggemann-Weinrich, Yvonne; Baumeister, Jochen; Krause, Daniel (Research Quarterly for Exercise and Sport)
Keywords: Nephrology; Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine; General Medicine

Efing, Christian (Hrsg.): Sprache und Kommunikation in der beruflichen Bildung. Modellierung – Anforderungen – Förderung. Frankfurt am Main: Lang, 2015 (Wissen – Kompetenz – Text, 9). – ISBN 978-3-631-66096-6. 289 Seiten, € 62,95. - Prikoszovits, Matthias (Informationen Deutsch als Fremdsprache)
Keywords: General Medicine

Sublinear signal production in a two-dimensional Keller–Segel–Stokes system - Black, Tobias (Nonlinear Analysis: Real World Applications)
Keywords: Applied Mathematics; Computational Mathematics; General Economics; Econometrics and Finance; General Engineering; General Medicine; Analysis

Tolerance Analysis of Adhesive Bonds in Crash Simulation - Schwarzkopf, G.; Bobbert, Mathias; Teutenberg, Dominik; Meschut, Gerson; Matzenmiller, A. (Procedia CIRP)
The influences of geometrical parameters like adhesive layer thickness and gap-filling on the mechanical properties of adhesively bonded joints are investigated by means of experimental studies with controlled parameter variations. In addition, corresponding simulation models are used to analyse these effects. As a result, the behaviour of joints under variation of manufacturing parameters can be reproduced with high accuracy. Furthermore, the validated simulation models are used to perform sensitivity analysis on a component-like specimen. Based on these studies, tolerance ranges can be specified and robust design optimisation can be carried out.
Keywords: General Medicine

Serum sclerostin and DKK1 in relation to exercise against bone loss in experimental bed rest - Belavý, Daniel L.; Baecker, Natalie; Armbrecht, Gabriele; Beller, Gisela; Bühlmeier, Judith; Frings-Meuthen, Petra; Rittweger, Jörn; Roth, Heinz J.; Heer, Martina; Felsenberg, Dieter (Journal of Bone and Mineral Metabolism)
Keywords: Endocrinology; Orthopedics and Sports Medicine; General Medicine; Endocrinology; Diabetes and Metabolism

Experimentelle und theoretische Untersuchung der Existenz von CuII, CuIIIund CuIVin Kupfercorrolen - Sinha, Woormileela; Sommer, Michael G.; Deibel, Naina; Ehret, Fabian; Bauer, Matthias; Sarkar, Biprajit; Kar, Sanjib (Angewandte Chemie)
Keywords: General Medicine

Nanometer Scale Electronic Device Integration Using Side-Wall Deposition and Etch-Back Technology - Hilleringmann, Ulrich; Assion, F.; Vidor, F. F.; Wirth, G. I. (Journal of Machine to Machine Communications)
Keywords: General Medicine

Effects of bandwidth feedback on the automatization of an arm movement sequence - Agethen, Manfred; Krause, Daniel (Human Movement Science)
Keywords: Experimental and Cognitive Psychology; Orthopedics and Sports Medicine; General Medicine; Biophysics

Musculoskeletal effects of 5 days of bed rest with and without locomotion replacement training - Mulder, E.; Clément, G.; Linnarsson, D.; Paloski, W. H.; Wuyts, F. P.; Zange, J.; Frings-Meuthen, P.; Johannes, B.; Shushakov, V.; Grunewald, M.; Maassen, N.; Bühlmeier, Judith; et al. (European Journal of Applied Physiology)
Keywords: Physiology (medical); Public Health; Environmental and Occupational Health; Orthopedics and Sports Medicine; General Medicine; Public Health; Environmental and Occupational Health; Physiology

Hybrid Technologies for Joining Ultra-high-strength Boron Steels with Aluminum Alloys for Lightweight Car Body Structures - Meschut, Gerson; Matzke, Marcus; Hoerhold, Réjane; Olfermann, Thomas (Procedia CIRP)
Keywords: General Medicine

Self-pierce Riveting and Hybrid Joining of Boron Steels in Multi-material and Multi-sheet Joints - Hahn, O.; Meschut, G.; Bergau, M.; Matzke, M. (Procedia CIRP)
Keywords: General Medicine

Evaluation of Damage to Carbon-fibre Composites Induced by Self-pierce Riveting - Meschut, G.; Gude, M.; Augenthaler, F.; Geske, V. (Procedia CIRP)
Keywords: General Medicine

Effects of model orientation on the visuomotor imitation of arm movements: The role of mental rotation - Krause, Daniel; Kobow, Sven (Human Movement Science)
Keywords: Experimental and Cognitive Psychology; Orthopedics and Sports Medicine; General Medicine; Biophysics

Von der mannigfaltigen Bedeutung der Reduktion nach Husserl - Luft, Sebastian (Phänomenologische Forschungen)
This paper takes a renewed look at Husserl’s method of the phenomenological reduction. It interprets “the reduction” as shorthand for the meaning of Husserl’s entire phenomenology in its mature stage. In the same way, the method of reduction might have different manners of execution but they are nevertheless guided by a common intent. The text takes its starting point by considering the different metaphors Husserl uses – the “flatland creatures” and the reduction as akin to a religious conversion – and spells out their implications, which lead me to consider their metaphilosophical significance. In this way, this article attempts a metaphilosophical reading of the meaning of the reduction in Husserl, which is equal to considering the meaning philosophy has for Husserl in the most general terms. In this way, some unorthodox reflections are carried out that shed new light on central phenomenological concepts, such as vidence and eidetic variation, phenomenology as a form of transcendental idealism, and the notorious problem of the lifeworld. In this way, Husserl’s phenomenology is interpreted as a peculiar representative of Enlightenment philosophy that restitutes a special notion of responsibility.
Keywords: General Medicine

Fast Nucleation and Growth of ZIF-8 Nanocrystals Monitored by Time-Resolved In Situ Small-Angle and Wide-Angle X-Ray Scattering - Cravillon, Janosch; Schröder, Christian A.; Nayuk, Roman; Gummel, Jeremie; Huber, Klaus; Wiebcke, Michael (Angewandte Chemie)
Keywords: General Medicine

Study on the Performance Enhancement of ZnO Nanoparticles Thin-Film Transistors - Vidor, Fábio Fedrizzi; Wirth, Gilson Inácio; Wolff, Karsten; Hilleringmann, Ulrich (ECS Transactions)
Due to the electrical, sensory and optical properties the interest on ZnO-based devices including thin-film transistors (TFT) aroused. The main concerns, when using ZnO nanoparticles (NP-ZnO) in TFT, are the low charge carrier mobility and the hysteresis when poly(4-vinylphenol) (PVP) is used as gate dielectric. It is well-known that the mobility in NP-ZnO films can be enhanced by the subsequent hydrothermal decomposition of zinc salts. The electrical behavior as a function of time and temperature is investigated, taking the NP-ZnO without addition of zinc acetate as reference. The addition of zinc acetate leads to a device with better performance, with increased drain current level and without the presence of the hysteresis in the transfer characteristic. The formation reaction was performed at a temperature of 200°C, which enables process compatibility to some plastic substrates.
Keywords: General Medicine

Das Zensurverfahren gegen Giuseppe Verdis Don Carlo vor der Römischen Inquisition - Höink, Dominik (Jahrbuch der Juristischen Zeitgeschichte)
Keywords: General Medicine; General Chemistry

Active Suppression of Torsional Oscillations - Böcker, Joachim; Amann, Notker; Schulz, Bernd (IFAC Proceedings Volumes)
Keywords: General Medicine

Meditationen, Geheimnisse, Zufälle: Messiaens Konzept der langage communicable - Grotjahn, Rebecca (Frankfurter Zeitschrift für Musikwissenschaft)
Keywords: General Medicine

Physikalische Chemie 1997 - Gradzielski, Michael; Kitzerow, Heinz-Siegfried; Hainze, Gürgen; Smie, Andreas; Krischer, Katharina; Blümich, Bernhard; Blümler, P. (Nachrichten aus Chemie, Technik und Laboratorium)
Keywords: General Medicine

Angular Dependence of Blue Phase Selective Reflection in the Electric Field - Heppke, G.; Kitzerow, Heinz-Siegfried; Krumrey, M. (Molecular Crystals and Liquid Crystals Incorporating Nonlinear Optics)
Keywords: General Medicine